2009
DOI: 10.1080/02770900802460548
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Interleukin-10 and Transforming Growth Factor-β in Children with Acute Exacerbation of Allergic Asthma

Abstract: Cytokine-mediated interactions among inflammatory cells may contribute to pathogenesis of allergic asthma. To understand the role of soluble interleukin-10 (IL-10) and transforming growth factor-beta (TGF-beta) on the disease activity and regulation in asthma, changes in serum concentrations of IL-10 and TGF-beta elaborated by activated T-lymphocyte before and after prednisolone therapy with clinical improvement were determined. Circulating levels of IL-10 and TGF-beta in sera from 16 normal control subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Although previous reports showed serum ECP [7,8,9,10] and serum or plasma cytokine/chemokine production [7,10,11,12,13,14,15,16,17,18,19] in acute exacerbations of asthma, this is the first report to show the profiles of ECP and 27 cytokines/chemokines in serum samples of patients with acute and stable asthma, and in controls. In this study, serum ECP was significantly elevated in acute asthma compared with stable asthma and controls.…”
Section: Discussionmentioning
confidence: 81%
“…Although previous reports showed serum ECP [7,8,9,10] and serum or plasma cytokine/chemokine production [7,10,11,12,13,14,15,16,17,18,19] in acute exacerbations of asthma, this is the first report to show the profiles of ECP and 27 cytokines/chemokines in serum samples of patients with acute and stable asthma, and in controls. In this study, serum ECP was significantly elevated in acute asthma compared with stable asthma and controls.…”
Section: Discussionmentioning
confidence: 81%
“…The difference in MDSCs levels in the asthma patients and the pneumonia patients suggest there is a difference between asthma which is a specific type of airway inflammation, and common airway bacterial infections. The published data indicated that monocytic (CD11b+Ly-6G-Ly-6GC high) MDSC increases IL-10 production through monocyte-dependent STAT1, iNOS and NO production, whereas granulocytic (CD11b+Ly6G+Ly-6C low) MDSC does this by a granulocyte-dependent ARG and ROS pathway [13], [16], [17], [18], [19], [20]. We analyzed the accumulation of NO and ARG/ROS, Table S3, and found that both the accumulation of NO and ARG/ROS increased in the asthma mice and the accumulation of them are all prominently down-regulated upon budesonide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 plays an important role in the onset of asthma, and the gene polymorphism of IL-12 is correlated to the risk index of asthma [19]. It has been showed that the IL-10 level in both asthmatic group and alleviated group was lower than control group [20], while another study reported that the IL-10 level in asthmatic children without a family history of asthma was comparable with that in healthy control group [21]. However, our study showed that asthmatic children expressed higher levels of IL-10 and lower levels of IL-12 compared to normal controls, budesonide-treated asthma patients, and pneumonia patients, while the latter three demonstrated no significant differences (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested that TGF-β, rather than IL-10, may be more important and serve as a biomarker of asthma control in atopic asthma (86). TGF-β is a pleiotropic cytokine with numerous functions that are vital in maintenance of pulmonary homeostasis, such as inhibiting Th2 and Th1 cell responses or inhibiting IgE production (87).…”
Section: Regulatory T Cellsmentioning
confidence: 99%